Toxicity of Euphorbia helioscopia pellets to two phytophagous molluscs, Theba pisana Müller, 1774 (Pulmonata: Helicidae) and Arion hortensis Férussac, 1819 (Pulmonata: Arionidae) - Harmouzi, Anjoud; Boughdad, Ahmed; El Ammari, Yassine; Chaouch, Abdelaziz (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
Harmful land snails and slugs are currently one of the most important threats facing agriculture in many parts of the world. Synthetic molluscicides are the main control method against these gastropods. However, dangers caused by these chemicals to the environment have led scientists to research for environmentally friendly alternatives. The objective of our work was to test and evaluate food pellets containing roots, stems, leaves or flowers of Euphorbia helioscopia against Theba pisana and Arion hortensis adults. Toxicity of the prepared pellets varied depending on plant organ and mollusc species tested. Pellets made of stems (LD50 = 1.35 g / 100 ml of agar at 2%) and leaves (LD50 = 1.39 g / 100 ml of 2% agar) proved more toxic to adult snails than those made of roots and flowers, which had no significant effects. In the case of slugs, pellets made of leaves (LD50 = 1.14 g / 100 ml of 2% agar) were more toxic than those made of stems (LD50 = 1.33 g / 100 ml of 2% agar), flowers (LD50 = 1.75 g / 100 ml of 2% agar) and roots (LD50 = 1.98 g / 100 ml of 2% agar). Compared to a synthetic product containing metaldehyde 5%, the results show that the use of these molluscicides derived from plants as pellets is environment- and healthconscious, targeted and economical. These products can be used in plant protection against phytophagous slugs and snails.
Keywords: Biopesticides; Molluscides; Euphorbia helioscopia; Pellets; Snails; Slugs; Toxicity